2011
DOI: 10.1111/j.1399-3054.2011.01525.x
|View full text |Cite
|
Sign up to set email alerts
|

Could shading reduce the negative impacts of drought on coffee? A morphophysiological analysis

Abstract: Based on indirect evidence, it was previously suggested that shading could attenuate the negative impacts of drought on coffee (Coffea arabica), a tropical crop species native to shady environments. A variety (47) of morphological and physiological traits were examined in plants grown in 30-l pots in either full sunlight or 85% shade for 8 months, after which a 4-month water shortage was implemented. Overall, the traits showed weak or negligible responses to the light × water interaction, explaining less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
1
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 52 publications
9
70
1
10
Order By: Relevance
“…This agrees with the fact that, in Granada, there are higher radiation, clear skies, and the soil is not water saturated (as was seen by the water soil content), which favor water uptake by the roots and its transport by the xylem due to the fact that it generates a high stomatal sensitivity to environmental changes (Rocha et al, 2004). Cavatte et al, (2012) reported that a low moisture content in the soil and high radiation in the day increase the nocturnal ability for hydration. When comparing the transpiration rate, the stomatal conductance and the water potential, a finer stomatal control was observed for Granada, evidenced by the fact that a slight decrease in stomatal conductance, caused a decrease in the transpiration that was clearly reflected in an increase in the water potential, which although also was observed in Chia, was less evident.…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with the fact that, in Granada, there are higher radiation, clear skies, and the soil is not water saturated (as was seen by the water soil content), which favor water uptake by the roots and its transport by the xylem due to the fact that it generates a high stomatal sensitivity to environmental changes (Rocha et al, 2004). Cavatte et al, (2012) reported that a low moisture content in the soil and high radiation in the day increase the nocturnal ability for hydration. When comparing the transpiration rate, the stomatal conductance and the water potential, a finer stomatal control was observed for Granada, evidenced by the fact that a slight decrease in stomatal conductance, caused a decrease in the transpiration that was clearly reflected in an increase in the water potential, which although also was observed in Chia, was less evident.…”
Section: Discussionmentioning
confidence: 99%
“…In all the analyses, the quantity of blue light applied was 10 % of the photosynthetically active radiation (PAR), in order to maximize stomatal opening. More details were described by Cavatte et al (2012).…”
Section: Determination Of Gas Exchangementioning
confidence: 99%
“…The total daily transpiration (TDT) was estimated by gravimetry, by means of the weight difference of the pots with a one-hour interval between 07:00 and 18:00 as described by Cavatte et al (2012).…”
Section: Physiological Variablesmentioning
confidence: 99%